PS-046 Materiovigilance ex ante risk management. (14th February 2016) - Dubromel, A; Charra, F; Bourge, X; Philibert, M; Locher, F; Derain, L
Abstract : Background: Since the publication on 6 April 2011 of the 'Decree on the quality management of medicinal treatment and drugs in health institutions', it has become a priority in hospitals. In addition, in the 2010 version of the High Authority of Health Certification manual, criterion 8d deals with the evaluation requirements and risk prioritisation based on defined methods, implementation of preventive, mitigation or recovery actions, staff training in risk analysis, and monitoring and measuring the effectiveness of the implemented actions. Purpose: It is in this context that the Organisation, Quality, User Relations Directorate of our health institution has requested that the medical device vigilance service initiate a project on quality management and develop a materiovigilance ex ante risk assessment tool. The chosen quality tool was a risk mapping, based on the FMEA method (failure mode effects analyses) which allows prioritisation of risks to identify actions for improvement and to develop an action plan. Material and methods: First the project leader contacted stakeholders to create a multidisciplinary group. Then an inventory of the service documentary system was performed. In parallel, the development of the risk mapping was started with analysis of the process and identification of the associated risks. The causal factors and impact of the risks on global process were analysed. Then a quotation of risk frequency and acceptability in terms of patient incidence was created in order to calculate a gross criticality. Finally, actions for improvement were identified. A risk quotation of feasibility of setting up these actions was developed in order to calculate a net criticality. Through this work, priority risks were identified. Results: Five major activities, about 50 associated risks and many scenarios were identified. Due to the risk mapping, three priority actions have been identified to be implemented: reinforce staff training, raise awareness on declaration and write service continuity procedures. These actions were included in the action plan for 2016. Conclusion: The development of this quality tool was made in the context of the certification of health institutions as well as in the context of a comprehensive approach to improve quality management and patient care in hospitals. References and/or Acknowledgements: Manuel de certification des établissements de santé v2010. HAS, 2011. No conflict of interest.